2010
DOI: 10.1038/jid.2010.191
|View full text |Cite
|
Sign up to set email alerts
|

Plakophilin-1 Localizes to the Nucleus and Interacts with Single-Stranded DNA

Abstract: Plakophilins (Pkp-1, -2, and -3) comprise a family of armadillo repeat-containing proteins first identified as desmosomal plaque components, in which they link desmoplakin to the desmosomal cadherins. In addition to their role in desmosomal cell-cell adhesion, Pkps also localize to the nucleus, where they perform unknown functions. Of the three Pkps, Pkp-1 is most readily detected in the nucleus, where it is localized to the nucleoplasm. Pkp chimeras containing the Pkp-1 head domain and Pkp-3 armadillo repeat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 39 publications
5
44
1
2
Order By: Relevance
“…For example, plakophilin 2 associates in some contexts with β-catenin 63 , αT-catenin 114 and the largest subunit of the RNA polymerase III holoenzyme (RPC155) 115 . Plakophilin 1 can bind to single-stranded DNA 116 . Much of the biological significance of these associations, as well as how plakophilins enter the nucleus in the absence of an obvious NLS, remains to be clarified.…”
Section: Other Armadillo Catenins In the Nucleusmentioning
confidence: 99%
“…For example, plakophilin 2 associates in some contexts with β-catenin 63 , αT-catenin 114 and the largest subunit of the RNA polymerase III holoenzyme (RPC155) 115 . Plakophilin 1 can bind to single-stranded DNA 116 . Much of the biological significance of these associations, as well as how plakophilins enter the nucleus in the absence of an obvious NLS, remains to be clarified.…”
Section: Other Armadillo Catenins In the Nucleusmentioning
confidence: 99%
“…36 In the current study, lower levels of PKP1 protein and RNA were associated with DM and disease-specific survival. Sobolik-Delmaire et al 37 demonstrated that unlike the other members of its family, PKP1 is not a major element in the assembly of desmosomes. Yet it is translocated into the nucleus, where it can bind single-stranded DNA even though it lacks a canonical nuclear localization sequence.…”
Section: Commentmentioning
confidence: 99%
“…PKP1 has been shown to associate with single-stranded DNA and may be involved in the response to DNA damage. It also interacts with the translation initiation factor eIF4A1 to promote translation (Sobolik-Delmaire et al, 2010; Wolf et al, 2010). Finally, our data support the hypothesis that PKP2 acts as a signaling scaffold that functionally links RhoA– and protein kinase C–dependent pathways to drive actin reorganization and regulate desmosome assembly (Bass-Zubek et al, 2008; Godsel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%